1999
DOI: 10.1152/ajpgi.1999.276.3.g743
|View full text |Cite
|
Sign up to set email alerts
|

Rat liver endothelial cell glutamine transporter and glutaminase expression contrast with parenchymal cells

Abstract: Despite the central role of the liver in glutamine homeostasis in health and disease, little is known about the mechanism by which this amino acid is transported into sinusoidal endothelial cells, the second most abundant hepatic cell type. To address this issue, the transport ofl-glutamine was functionally characterized in hepatic endothelial cells isolated from male rats. On the basis of functional analyses, including kinetics, cation substitution, and amino acid inhibition, it was determined that a Na+-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…Among the amino acids found to be significantly affected in this study are glutamine and arginine, both of which have been reported to be either beneficial or “conditionally essential” after burn injury [7], [37], [38]. This is also consistent with prior findings of burn injury-induced increases in the expression of amino acid transporters for glutamine and arginine in the liver [8], [39], [40]. Glycine and methionine were also upregulated, and therefore may be potential candidates to further examine as nutritional supplements.…”
Section: Discussionsupporting
confidence: 90%
“…Among the amino acids found to be significantly affected in this study are glutamine and arginine, both of which have been reported to be either beneficial or “conditionally essential” after burn injury [7], [37], [38]. This is also consistent with prior findings of burn injury-induced increases in the expression of amino acid transporters for glutamine and arginine in the liver [8], [39], [40]. Glycine and methionine were also upregulated, and therefore may be potential candidates to further examine as nutritional supplements.…”
Section: Discussionsupporting
confidence: 90%
“…2 summarizes the main pathways leading to the production of the metabolites that were measured in the present work. These cells are able to express glutamine synthetase (18), which is also found in Kupffer and endothelial cells (4,29). Enzyme gradients along the hepatic acinus, however, are not represented.…”
Section: Methodsmentioning
confidence: 99%
“…Glutamine has the added value to contribute both its carbons and nitrogens to ECs’ metabolism (though the relative importance of both in vessel sprouting remains to be determined) and can therefore serve different, mostly biosynthetic metabolic fates 30 . ECs express the solute carrier family 1 member 5 (SLC1A5) to take up glutamine and were reported to have high glutaminase (GLS) activity 31, 32 ; this enzyme converts glutamine to glutamate in the first and rate-limiting step of glutaminolysis (the series of reactions that serves to supply glutamine carbons to the tricarboxylic acid (TCA) to replenish intermediates that were used for biosynthesis purposes (anaplerosis)) (Fig. 1).…”
Section: Ec Metabolism In Health: Driving Vessel Sproutingmentioning
confidence: 99%